Effervescent Granule Formulation of Bitter Melon Extract (Momordica charantia L.) with Gelatin as A Wet Granulation Binder - Setia Wati; Dwi Saryanti (Universitas Muhammadiyah Surakarta, 2019)
Bitter melon plants (Momordica charantia L.) have a bitter taste and are used as medicinal plants as diabetes, so effervescent granule preparation is made because it can be given to people who have difficulty swallowing tablets or capsules. This study to make effervescent granules formulation of bitter melon with variations the concentration of gelatin as a binder. Gelatin will produce granules of uniform size and have stronger binding capacity between particles than starch and PVP. The method of making effervescent granules was carried out by wet granulation separately. Effervescent granules are formulated with gelatin concentrations of 3%, 6% and 9%. The granules obtained were carried out by organoleptic evaluation, flow time, tapping test, water content, pH test, dissolution time and taste response. The result of evaluation physical properties obtained brown granule shape, while the result of testing the flow time, tapping test, pH test, dissolved time obtained the results that meet the requirements and moisture content tests did not meet the requirements because the use of hygroscopic acids other than that affected by the process during granule making effervescent. The taste respons test was carried out on 20 panelists, formula III had a sour taste and was preferred. Based on these results the best formula of effervescent granules is formula III because the higher the concentration of gelatin will increase the binding capacity between particles, so that the friction force between particles becomes more complicated and the flow rate gets better, and provide a sour taste so that the bitter taste of the bitter melon can be covered.